Safe Skin Management during Open Hepatectomy in a Patient with Recessive Dystrophic Congenital Epidermolysis Bullosa - Ikuo Watanobe; Hiroko Kida; Yuuki Sekine; Masaya Kawai; Shozo Miyano; Michio Machida; Toshiaki Kitabatake; Hiroyuki Sugo; Yoshifumi Lee; Kuniaki Kojima (Case Reports in Surgery)
Congenital epidermolysis bullosa is a rare, genetic condition in which even slight stimulation can cause blistering of the skin or mucosa. While previous reports of treatments requiring general anesthesia in these patients were focused on anesthesia-related procedures, such as endotracheal intubation, no report has described specific management required for these patients during surgery, such as preparation of the surgical site, fixation of infusion lines and other tubes, and adjustment of the operation table. This is probably the first report to address these issues. This report presents a case of recessive dystrophic congenital epidermolysis bullosa in which open hepatectomy was safely performed.